Culture temperature modulates half antibody and aggregate formation in a Chinese hamster ovary cell line expressing a bispecific antibody. Issue 12 (5th October 2018) - Gomez, Natalia; Wieczorek, Agatha; Lu, Fang; Bruno, Richele; Diaz, Luis; Agrawal, Neeraj J.; Daris, Kristi
Abstract: Therapeutic bispecific antibodies are formed by assembly of multichain polypeptides. In general, a bispecific antibody has two different light chains and two different heavy chains that fold and correctly pair via engineered interchain interactions. Because of some incorrect assembly, product‐related impurities can be prevalent (e.g., half molecules, mispaired light chains, homodimers), requiring its removal during subsequent purification. In this study, we investigated the modulation of impurity levels in a stable Chinese hamster ovary cell line X expressing a bispecific antibody A formed by two light chains (LC1 and LC2) and two heavy chains (HC1 and HC2) that assembled intracellularly into a heterodimer (LC1–HC1 + LC2–HC2) via engineered charged residues. Cell line X exhibited the best volumetric productivity, growth, and viability in culture compared with other clones but also showed higher levels of half antibody species (>10%); therefore, to minimize process yield loss, better understanding, and control of impurity formation was pursued. We found this cell line decreased half antibody levels from 16% to 1% when temperature changed from 36°C to 32.5°C or 31.5°C. However, lower temperature also increased high‐molecular‐weight (HMW) species from 4% to 12%. To determine the impurity species composition, we characterized enriched fractions with half antibody or HMW. Intact mass spectrometry analysis revealed half antibody was LC2–HC2, whereas HMW was a mixture with 50% as LC1–HC1 homodimer. Results suggested LC2–HC2 was easily folded and could be secreted as half antibody, especially at 36°C. On the contrary, LC1–HC1 was more susceptible to misfold or aggregate, a phenomenon more acute for cell line X at lower culture temperature because of 60% increased LC1 and HC1 messenger RNA levels. Although temperature modulation was cell line X‐specific, the propensity of LC2–HC2 to form half antibodies and LC1–HC1 to aggregate appeared in other cell lines also expressing bispecific antibody A, suggesting an amino‐acid sequence‐dependent mechanism. In summary, impurity formation in cell line X was temperature‐dependent and was influenced by different molecule characteristics between the LC1–HC1 and LC2–HC2 parts. Ultimately, we selected a biphasic cell culture process with a growth phase followed by a lower temperature phase to improve product quality and purification yield. Abstract : Gomez and coworkers studied the formation of product‐related impurities in a CHO cell line expressing a bispecific antibody formed by two light chains (LC1, LC2) and two heavy chains (HC1, HC2). In particular, cell culture temperature modulated formation of half bispecific antibody (half B‐Ab) and high molecular weight (HMW) species. More uniquely, both impurity levels were inversely correlated with increasing 1 to 16% half B‐Ab and decreasing 12 to 4% HMW with increasing temperature.